Electrical and photoelectric properties of photocell based on two Schottky barrier contacts Al-p-Si and Ti-p-Si - A. I. Blesman; R. B. Burlakov; D. A. Polonyankin (Омский научный вестник)
Task of studies is a development of the structure and way of the fabrication of the photocell capable to take a radiation or in near infrared region of the spectrum (1–1,4) microns, or in the field of (0,5–1,4) microns. Way of fabrication and results of studies of photoelectric features of two spectrum photocell based on two Schottky barrier contacts Al-p-Si and Ti-p-Si, situated on opposite parties Si plate are considered.